Internet of Things and Big Data Analytics Toward Next-Generation Intelligence - Dey, Nilanjan; Hassanien, Aboul Ella.; Bhatt, Chintan; Ashour, Amira S.; Satapathy, Suresh Chandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book highlights state-of-the-art research on big data and the Internet of Things (IoT), along with related areas to ensure efficient and Internet-compatible IoT systems. It not only discusses big data security and privacy challenges, but also energy-efficient approaches to improving virtual machine placement in cloud computing environments.  Big data and the Internet of Things (IoT) are ultimately two sides of the same coin, yet extracting, analyzing and managing IoT data poses a serious challenge. Accordingly, proper analytics infrastructures/platforms should be used to analyze IoT data. Information technology (IT) allows people to upload, retrieve, store and collect information, which ultimately forms big data. The use of big data analytics has grown tremendously in just the past few years. At the same time, the IoT has entered the public consciousness, sparking people's imaginations as to what a fully connected world can offer.  Further, the book discusses the analysis of real-time big data to derive actionable intelligence in enterprise applications in several domains, such as in industry and agriculture. It explores possible automated solutions in daily life, including structures for smart cities and automated home systems based on IoT technology, as well as health care systems that manage large amounts of data (big data) to improve clinical decisions. The book addresses the security and privacy of the IoT and big data technologies, while also revealing the impact of IoT technologies on several scenarios in smart cities design. Intended as a comprehensive introduction, it offers in-depth analysis and provides scientists, engineers and professionals the latest techniques, frameworks and strategies used in IoT and big data technologies. .
Internet of Things based Wireless Body Area Network in HealthCare -- Mobile Sensor Networks and Robotics -- Big Data Analytics with Machine Learning Tools -- Real time big data analytics to derive actionable intelligence in enterprise applications -- Revealing Big Data Emerging Technology as Enabler of LMS Technologies Transferability -- Performance Evaluation of Big Data and Business Intelligence Open Source Tools: Pentaho and Jaspersoft -- IoT Gateway for Smart Devices -- Smart manufacturing in the Internet of Things era -- Home Automation using IoT -- A Prototype of IoT-Based Real Time Smart Street Parking System for Smart Cities -- Smart Irrigation: Towards Next Generation Agriculture -- Greening the future: Green Internet of Things (GIoT) as a key technological enabler of sustainable development -- Design of Cloud-Based Green IoT Architecture for Smart Cities -- Internet of Things Shaping Smart Cities: A Survey -- Big Data Analytics for Smart Cities -- High Capacity and Secure Electronic PatientRecord (EPR) embedding in color images for IoT driven healthcare systems -- Practical Techniques for Securing the Internet of Things (IoT) Against Side Channel Attacks -- Framework of Temporal Data Stream Mining by Using Incrementally Optimized Very Fast Decision Forest -- Sentiment Analysis and Mining of Opinions -- A Modified Hybrid Structure for Next Genration Super High Speed Communication using TDLTE and Wi-Max Pranay.
Keywords: Computational intelligence; Big data; Quantitative research; Artificial intelligence; Application software; Computational Intelligence; Big Data; Data Analysis and Big Data; Artificial Intelligence; Computer and Information Systems Applications